2000
DOI: 10.1002/(sici)1097-0088(200001)20:1<105::aid-joc459>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting Indian summer monsoon rainfall by outgoing longwave radiation over the Indian Ocean

Abstract: The satellite derived outgoing longwave radiation (OLR) over the Indian Ocean (30°N–30°S and 40°E–100°E) from 1974 to 1996 has been analysed for the relationship with the Indian summer monsoon total (June–September) rainfall. The OLR of two regions appears to be related to summer monsoon rainfall. One of the regions is located over the Head Bay of Bengal (near 22.5°N and 92.5°E) during May and the other one over the south Indian Ocean (near 30°S and 97.5°E) during April. The average OLR (index) for these two r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 15 publications
(15 reference statements)
0
8
0
1
Order By: Relevance
“…On the other hand, the stronger SH insolation in boreal winter and early spring heats the southern Indian Ocean locally (see Figs. 4b,d) but does influence the subsequent Indian summer monsoon through a comparatively longer memory and interhemispheric ocean-atmospheric circulation as Prasad et al (2000) suggested. Second, the summer monsoon is much stronger than the winter monsoon over South Asia (Wang et al 2003a).…”
Section: Summary and Discussionmentioning
confidence: 90%
“…On the other hand, the stronger SH insolation in boreal winter and early spring heats the southern Indian Ocean locally (see Figs. 4b,d) but does influence the subsequent Indian summer monsoon through a comparatively longer memory and interhemispheric ocean-atmospheric circulation as Prasad et al (2000) suggested. Second, the summer monsoon is much stronger than the winter monsoon over South Asia (Wang et al 2003a).…”
Section: Summary and Discussionmentioning
confidence: 90%
“…This may lead to relatively warmer air temperatures over the region (R1 in the present study) resulting in positive TI 1 , favoring the above-normal ISMR, while negative TI 2 may be due to excess cooling in May over R2. Based on Outgoing Longwave Radiation (OLR) data, Prasad et al (2000) showed that, when the north Bay of Bengal region (R2 in present study) experiences more convective activities during May, the subsequent ISMR happens to be above normal. Such frequent convective activities induce a sudden drop in temperature and rise in pressure due to descending cold air from aloft.…”
Section: Interannual Variability Of Indices and Ismrmentioning
confidence: 64%
“…The relationship between the temperature anomalies and ISMR should be tested for its stability before using it in prediction of the ISMR, since a recent study by Prasad et al (2000) found that some predictors of the ISMR have been losing the power of prediction of ISMR during recent decades. In order to test the consistency and stability of the relationship between the thermal indices with the ISMR, we have used the 31 years sliding window technique.…”
Section: Stability Of the Relationship Between Ismr And Thermal Indicesmentioning
confidence: 99%
“…The relationship between the temperature anomalies and the ISMR should be tested for its stability before using it in prediction of the ISMR, since a recent study by Prasad et al (2000) has found that some predictors of the ISMR lose the power of prediction of ISMR during the recent decade.…”
Section: Stability Of the Relationship Between Ismr And Temperature Amentioning
confidence: 99%